IMPLEMENTATION OF GOOD GOVERNANCE AND MOTIVATION IN IMPROVING SERVICE QUALITY: THE ROLE OF JOB SATISFACTION AS A MEDIATING VARIABLE (Study at the Badung Regency Cultural Office) - I Gede Krisnayasa; I.G.A.A. Dewi Sucitawathi Pinatih (RADJA PUBLIKA, 2025)
This study aims to analyze the effect of Good Governance and work motivation on public service quality, as well as the role of job satisfaction as a mediating variable. The research population consisted of all employees of the Cultural Office of Badung Regency, including Civil Servants (PNS) and Government Employees with Work Agreements (PPPK). A total of 107 respondents were selected using Slovin's formula. Data collection was conducted through questionnaires, and analysis was performed using Structural Equation Modeling-Partial Least Squares (SEM-PLS).The results indicate that Good Governance has a positive and significant effect on service quality, as does work motivation. Job satisfaction was found to play a significant mediating role in the relationship between Good Governance, work motivation, and service quality. These findings confirm that transparent, accountable, and participatory governance practices, alongside enhanced employee motivation, contribute to increased job satisfaction, which in turn strengthens the quality of public services. The implications of this study suggest the need to reinforce Good Governance principles, implement evaluation and innovation in human resource management, and address employee motivation and job satisfaction to create more responsive, reliable, professional, and citizen-oriented public services. This research provides empirical evidence crucial for developing sustainable public service policies in Badung Regency.